2016
DOI: 10.1021/acsnano.5b07697
|View full text |Cite
|
Sign up to set email alerts
|

Live Bacterial Physiology Visualized with 5 nm Resolution Using Scanning Transmission Electron Microscopy

Abstract: It is now possible to visualize at nanometer resolution the infection of a living biological cell with virus without compromising cell viability using scanning transmission electron microscopy (STEM). To provide contrast while preserving viability, Escherichia coli and P1 bacteriophages were first positively stained with a very low concentration of uranyl acetate in minimal phosphate medium and then imaged with low-dose STEM in a microfluidic liquid flow cell. Under these conditions, it was established that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Investigating biological systems has additionally been a major interest of LC-TEM ( 31 , 32 ), although the role of irradiation history on soft and organic samples is of even greater concern than for other systems. Thus, determining whether structural and morphological changes are actual physiological events or artifacts of the electron beam damaging the sample is a necessary consideration for any LC-TEM experiment on a biological sample.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating biological systems has additionally been a major interest of LC-TEM ( 31 , 32 ), although the role of irradiation history on soft and organic samples is of even greater concern than for other systems. Thus, determining whether structural and morphological changes are actual physiological events or artifacts of the electron beam damaging the sample is a necessary consideration for any LC-TEM experiment on a biological sample.…”
Section: Resultsmentioning
confidence: 99%
“…57 Previous works have shown that the effects of changes in pressure, temperature, free radical generation, and exposure to the electron beam itself are non-significant under low electron doses for large samples, such as those containing E. coli, as implemented here (SI notes). 57,59,61,[65][66][67][68][69][70][71][72][73][74][75][76] Thus, previous works indicate that E. coli 1) maintain their metabolic processes, 2) maintain their cell envelopes, and 3) continue to undergo binary fission within liquid-phase TEM. 57,59,61,[65][66][67][68][69][70][71][72][73][74][75][76] Liquid-phase TEM (Figures 3 and S2) provides further evidence of the penetration of nanoprotrusions in E.coli, as also observed forensically with conventional TEM (Figures 2 and S1).…”
Section: Cell Wallmentioning
confidence: 99%
“…Liquid cell TEM has been used alone or associated with optical microscopy to image in vivo systems, such as magnetotactic bacteria, 54 the infection of a living biological cell with virus, 55 movements of Au nanoparticles embedded in MDCK cellular matrix in solution, 56 delivery of nanoparticles into cancer cells, 57 etc. For examples, in 2014, Woel et al have combined liquid cell TEM with fluorescence microscopy to image magnetotactic bacteria in liquid.…”
Section: Dynamical Processes In Vivomentioning
confidence: 99%